Effect of Market Gardening on Monetary Poverty among Rural Households in Senegal - Nana, Tégawendé Juliette; Pouye, Rokhy; Ndoye, Fatou; Gbenou, Kpégo Didier Anatole (International Journal of Economics and Financial Issues, 2026)
The objective of this study is to analyse the effects of market gardening on the monetary poverty of rural households in Senegal, particularly in the Sedhiou region. Data was collected from 280 households. A comparison of household monetary poverty indices calculated using the method developed by Foster, Greer and Thorbeck shows that poverty is more pronounced among non-market gardening households and that market gardening reduces the incidence of poverty by the 1.14%, its depth by 5.52% and its severity by 6.07%. Analysis of the Lorentz curve shows that market gardening helps to reduce income inequality within households that practise it. It also appears that market gardening is an important source of monetary income for households, as it accounts for 21% of their agricultural monetary income and 9% of their total monetary income. Policies promoting the development of market gardening would contribute significantly to increasing farmers' incomes and reducing monetary poverty.